Hernia de Amyand en cirugía electiva de hernia inguinal: Reporte de un caso y revisión de la literatura - Hurtado-Frisancho, Daniel (2026)
Introduction: Amyand's hernia (AH) is rare; it is defined as the presence of the cecal appendix (CA) within the inguinal hernia sac. Case report: We present the case of a 64-year-old man who underwent elective surgery for a giant right inguinoscrotal hernia. The hernia was found to have loops of bowel with the normal-appearing AC attached to the sac. During surgery, the loop was released and reintroduced into the cavity, completing the surgery with a Lichtenstein hernioplasty. The patient presented residual scrotal edema and hematoma, which ultimately resolved with drainage and orchiectomy. Conclusion: Preoperative diagnosis of AH is difficult; it may be suspected in chronic hernias with acute abdominal pain. However, diagnosis is generally made intraoperatively. There is no consensus on management; rather, there are classifications that serve as a guide for the surgeon; however, each case must be individualized.